The analysis, evaluation and design of an active DC power filter for a HVDC system - Holtzhausen, H. N.(Hermanus Nicolaas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1998.